An aryl-triazole foldamer containing a 1, 8-naphthalimide fluorescent motif for monitoring and enhancing the anion-induced folding. Issue 37 (11th September 2017) - Yang, Ling; Wang, Ying; Che, Yanke; Jiang, Hua
Abstract : A 1, 8-naphthalimide fluorescent motif was found to facilitate folding and to largely enhance halogen anion binding for an aryl-triazole foldamer. Abstract : A novel aryl-triazole foldamer incorporating a 1, 8-naphthalimide motif was designed and synthesized. 1 H NMR, UV-vis and fluorescence spectroscopic titration experiments with halide anions (Cl −, Br −, I − ) demonstrated that the π–π stacking interaction of 1, 8-naphthalimide building blocks could largely enhance the folding and anion binding of the foldamer.